PENGARUH PERPUTARAN KAS, QUICK RATIO DAN PERPUTARAN TOTAL ASET TERHADAP NET PROFIT MARGIN PADA PT. TRINITY INTERLINK PERIODE 2014 - 2018 - AGNES LUKITA; PIPIN RIZKI SUCIANI; METYRIA IMELDA HUTABARAT; EDY FIRMANSYAH (LP2MTBM MAKARIOZ, 2020)
In general, the success of a company in carrying out its activities is often based on the level of net profit margin obtained. Netprofit margin is a ratio used to show a company's ability to generate net profits. Factors affecting Net profit margin are cashturnover, quick ratio and total asset turnover. This research is a quantitative descriptive study. Samples were taken with asaturated sampling technique that is a total of 60 financial statement data. Data collection techniques using documentationand research models used are multiple linear regression. The results of the research with simultaneous hypothesis testingshow that together cash turnover, quick ratio and total asset turnover have significant and significant effect on net profitmargin. Hypothesis testing partially shows that cash turnover and quick ratio have no significant positive effect on net profitmargin while total assets turnover has a significant positive effect in PT. Trinity Interlink for the 2014-2018 period. Thehypothesis determination coefficient value is 0.114. This shows that 11.4% of the variation in the variable net profit margincan be explained by variations in the variable cash turnover, quick ratio and total asset turnover while the rest of (100% -11.4% = 88.6%) is a variation of other variables such as Solvency (DER) and Debt to Asset Ratio which are not explained inthis study.